Usulan Perbaikan Strategi Pemasaran Berbasis Reseller dengan Metode Analysis SWOT untuk Meningkatkan Volume Penjualan - 10070214056, Nopriyandi; Dewi Shofi Mulyati (UNISBA Press, 2024)
Abstract. Regional RIS is a reseller business that has been running for ±5 years. The sales system is carried out by resellers. To meet operational costs every month, the sales target is at least 4,000 pcs per month. The target is set based on the calculation factor of monthly operating costs required by RIS Regional. To meet operational costs, RIS Regional sets monthly sales at 4,000 units. Currently, Regional RIS conducts a product sales marketing system in a conventional way or has not used technology. So that sales cannot meet the target. With the conduct of this research, it is expected to determine the strategy implemented to increase RIS Regional revenue and know the internal and external conditions of the company. This study used the SWOT analysis method. SWOT analysis is efficient of various variables to know the procedures of the organization.